Clinico-Epidemiology, Risk Factors and Biochemistry of Nonalcoholic Fatty Liver Disease in Medicine OPD of A Tertiary Hospital (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Non Alcoholic Fatty Liver Disease (NAFLD) is one of the major causes of end stage liver disease worldwide and increasing in Bangladesh day by day. The study was conducted in Medicine Outpatient Department (OPD) of Chittagong Medical College Hospital to observe the clinic-epidemiology, risk factor and biochemical changes in patients with sonographyically proven NAFLD.Materials and methods: This was a prospective observational study.Patients presented with ultrasonography having NAFLD were enrolled and case record form were filled up after examination and investigations. Data were analyzed by SPSS 25. For statistical significance students t Tests (Continuous variables) and chi square tests (Categorical variables) were done where appropriate.Results: Total patients were 110, 71.8% were male, mean age were 40.1±9.5 years, 92.7% were obese though other risk factors were present with variable frequencies. 72.7% were symptomatic whether abdominal discomfort was highest of clinical symptoms that they had (58.2%). Triglyceride was more than 150 mg/dl in 81.8% cases and there was hyper transaminasemia in 80% cases.Conclusions: This was a small study and there was no histopathologically proven cases but was to do an screening in OPD. Further study would be required to conclude as hypertriglyceridemia and abdominal obesity are the risk factors in NAFLD cases.JCMCTA 2021 ; 32 (1) : 4-8